Nineteenth-century French collections of skulls and the cult of bones - Dias, N. (Nuncius: Journal of the Material and Visual History of Science, 2012)
This paper attempts to examine nineteenth-century French skull collections and to shed light on how, why, and when they came to play such a significant intellectual role in physical anthropology. It also seeks to analyze the notion of series of skulls and the sequential arrangement of skulls. It argues that this sort of collection gained particular relevance in Republican France, where the cult of dead bodies was replaced by the secular cult of bones.